Ferromagnetic ordering, magnetic and magnetotransport properties of R1−xSrx(Mn1−x/2Sbx/2)O3 (R = La, Pr, Nd, Sm, Eu) manganites. (6th June 2018) - Troyanchuk, I O; Bushinsky, M V; Tereshko, N V; Sirenko, V A; Sikolenko, V; Schorr, S; Ritter, C; Franz, A
Abstract: Neutron diffraction, magnetic and magnetotransport studies of perovskites R 1 − x 3 + Sr x 2 + ( Mn 1 − x / 2 3 + Sb x / 2 5 + )O3 (R = La, Pr) were carried out. It is shown that for x ∼ 0.2 systems undergo a transition from an antiferromagnetic state (x = 0) to a ferromagnetic state. In the case of the R = La series a structural transformation from the O ′-orthorhombic phase (x = 0) to the O -orthorhombic one occurs, which is due to orbital disordering. At x ≥ 0.6 cluster spin glass like phases arise due to the competition between antiferromagnetic and ferromagnetic interactions, as well as due to the strong diamagnetic dilution. In case of the R = Pr series the structural transition into the O -orthorhombic phase was not observed under (Sr, Sb) codoping. As the ionic radius of the rare-earth ion decreases in the series R0.7 Sr0.3 Mn0.85 Sb0.15 O3 the crystal structure distortion increases and the ferromagnetic state (R = La, Pr, Nd) is gradually transformed into a spin glass like state (R = Sm, Eu). The ferromagnetic compounds are insulators and exhibit a large magnitude of the magnetoresistance apparently associated with very small amount of Mn 4+ ions. The covalent component of the chemical bond and e.g.-orbitals disordering/mixing are assumed to be responsible for ferromagnetism in the compounds under study.